Toxicidad aguda del Tributilestaño (TBT) en dos gasterópodos marinos comestibles - Primost, Monica Angelina (2015)
Buccinanops globulosus and Trophon geversianus are high and low sensitive to TBT. LD50 was 5.41 and 6.21 μgTBT.g-1bw for B. globulosus and T. geversianus respectively, denoting high resistance to TBT acute exposure. These results can be used for future imposex induction experiments.